Penjadwalan Proyek Konstruksi Perumahan Menggunakan Metode Queuing System - Adnan Fadjar; Fahirah F; Ajeng Listianti; Ni Made Ayu Juli Andjani; Fritswel Ratmady Payung (Universitas Kristen Indonesia Paulus, 2026)
Housing development project is a construction activity characterized by repetitive construction activities, as the models and sizes of the houses built are generally similar and constructed repeatedly within a limited area. The conventional scheduling method, the Critical Path Method (CPM), is frequently applied in construction projects, however, CPM is less effective for repetitive construction as in housing development project because it does not account for the number of work units waiting to be processed (queuing). This study aims to analyze the application of the queuing system/queueing method in the planning and control of housing construction project schedules in Palu City, Indonesia. The research adopts a quantitative approach with descriptive and predictive analyses, utilizing field observations, interviews, and document analysis. Housing construction activity data are analyzed using the CPM and subsequently compared with a queuing system model through computer simulation. The results indicate that the queuing system method represents workflow more realistically than CPM, particularly in accounting for waiting times and production capacity at each construction stage. This approach is expected to enhance time and resource efficiency in repetitive housing construction projects and to contribute to the development of construction management based on production system principles.